Legal Protection for Vehicle Owners in Cases of Default in Car Rental Agreements - Rizky Perdana Bayu Putra (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2025)
This study investigates the phenomenon of default in car rental agreements and its legal implications for vehicle owners. The research aims to analyze the various forms of default, identify the underlying factors, and evaluate the adequacy of legal protection mechanisms available to owners. Employing an empirical legal research method, the study draws on semi-structured interviews with car rental business owners, vehicle renters, legal practitioners, and law enforcement officers. The findings indicate that the most frequent types of default include delays in returning the vehicle, non-payment of rental fees, misuse of vehicles beyond contractual terms, and, in severe cases, fraudulent conduct resulting in the loss of vehicles. It was also revealed that rental business owners often depend on incomplete or informal agreements, thereby weakening their legal standing in dispute resolution. From a legal perspective, rental agreements are generally treated as civil matters, but circumstances involving fraud or embezzlement may shift the issue into the criminal domain. Law enforcement officers highlight the difficulties in distinguishing between civil default and criminal offenses, often resulting in prolonged legal processes. The study concludes that current legal protection for vehicle owners remains inadequate, both preventively and repressively. Preventive measures require the establishment of comprehensive written agreements with clear provisions regarding obligations, penalties, and dispute resolution mechanisms. Meanwhile, repressive measures necessitate improved coordination between civil and criminal law enforcement. Strengthening contractual clarity and enhancing legal awareness among both owners and renters are critical steps toward reducing default risks and promoting legal certainty in vehicle rental practices.